Perkembangan Pasar Modal Syariah di Indonesia: Potensi, Tantangan, dan Regulasi dalam Investasi Berbasis Syariah - Selasi, Dini; Hernawati , Rita (FEB Universitas Maritim Semarang, 2024)
One of the most important instruments in economics is the sharia market which offers alternative investment options in accordance with Islamic sharia principles. The purpose of this study is to explain the concept of the Indonesian sharia market, the mechanisms involved, and the potential and challenges faced during its development. The method used in this study is a literature study using qualitative descriptive analysis, namely analyzing various factors, laws, and current developments related to the sharia market. The findings of this study indicate that the Indonesian sharia market has experienced significant growth due to stricter regulations from the Financial Services Authority (OJK) and the National Sharia Council-Indonesian Ulema Council (DSN-MUI). However, there are still several problems in this market, such as the lack of public understanding of sharia principles and gaps in available sharia products. Nevertheless, the Indonesian sharia capital market has a lot of potential, including the ability to increase public awareness of sharia investment and the various investment products available.